HEAVY METALS RISK ASSESSMENT OF TAILINGS COLLECTED FROM ANDACOLLO CITY, NORTHEN CHILE - Copaja, Sylvia Violeta; Muñoz, Francisco (Journal of the Chilean Chemical Society, 2023)
Throughout human history, passive mining residues have increased the levels of heavy metals or metallic trace elements in different environmental matrices. These elements, having the ability to accumulate, generate potentially toxic sites, and sometimes affecting people’s health. In Chile, metal mining is concentrated between the Administrative Regions IV and VI. Mine tailings constitute the toxic residues composed of heavy metals, which in many occasions are deposited in areas neighboring human settlements and are a health hazard for the inhabitants. When the entire mineral is extracted from a copper mine, only 2 % is used; the rest is cast off as different types of waste: 50 % sterile, 44 % tailings and 4 % slag. In this work, the concentrations of metallic trace elements such as: Al, As, Cd, Cr, Cu, Fe, Hg, Mn, Mo, Ni, Pb, Zn were studied in 6 sites of the largest tailings located within Andacollo city, Northern Chile. The sampling points were recorded using GPS geographic coordinates and, in the laboratory, they were characterized determining: pH, electrical conductivity, soluble organic carbon, total organic carbon, available phosphorus, boron, total nitrogen and capacity cation exchange. The concentrations of metallic trace elements in the tailings were quantified through the analysis of two of its fractions, total fraction and soluble fraction. Metals in both fractions ware determined by atomic absorption spectrophotometry (AAS). The physicochemical characterization of the tailings allowed establishing a profile of the environmental conditions of the sampled sites. The sites that presented a higher concentration of metals in the total fraction correspond to sites 4 and 6, while the sites that presented a higher concentration of metals in the labile fraction correspond to sites 2 and 6. Cu, Hg and Mo where the metals with the mayor Environmental risks assessment in all of sites.